Managing information and information-related technology: Enabling decision-making in flood management - Maidin, Siti Sarah; Othman, Marini; Ahmad, Mohammad Nazir; Arshad, Noor Habibah (Convergence Information Society(CIS), 2014)
It is recognized that Malaysia must establish effective flood management (FM) practices in order to reduce the impact of disasters upon the country’s economic development and growth. This article seeks to examine the non-structural aspects of FM. To date, governance has been identified as a crucial element by which to drive effective management of floods. The aim of this paper is to, namely: identify the current governance structure in the implementation of FM; identify the challenges in the current structure and propose a governance framework to oversee FM. The framework is designed to be constructed based on the analysis of current good practices which address issues surrounding FM. It is also based on a study conducted on the situation and status of the Malaysian flood governance and FM, specifically: its governance of agencies involved; coordination and interactions between the agencies; as well as the gathering and storage, controlling and monitoring, use, managing and sharing of information. A case study based on FM agencies in Malaysia which focused on their activities and interaction is presented in an attempt to lend understanding to the FM situation in Malaysia. A framework based on COBIT is justified as being suitable based on the gaps and challenges identified in the case study. It is hoped that further efforts will be channeled towards improving the framework.